Being at large : freedom in the age of alternative facts - Zabala, Santiago, 1975- (McGill-Queen's University Press, 2020)
"Politicians and philosophers presenting themselves as the ultimate bearers of truth and reality have created unprecedented technological, cultural, and political framings. This new order conspires to undermine the interpretive practices of open-ended critique, normalizing a sense of threat to preserve control. The greatest emergency has become the absence of emergencies. Tracing an intellectual alliance between academics such as Jordan Peterson and Christina Hoff Sommers and right-wing populist politicians such as Donald Trump and Marine Le Pen, this book denounces framings that make a claim to objectivity. With the help of contemporary thinkers including Bruno Latour, Judith Butler, and Giorgio Agamben, as well as discussion of the Cambridge Analytica whistleblower Christopher Wylie and the emergency of biodiversity loss due to climate change, Santiago Zabala illustrates that the twenty-first-century question is not whether we can be free, but how to be at large--unconstrained by the new realist order. Being at Large demonstrates the anarchic power of hermeneutics, calling for interpretive disruptions of the authoritarian narrative as a way of reclaiming freedom in the age of alternative facts."--